FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PREMENSTRUAL SYNDROME DI MASA PANDEMIC COVID19 PADA MAHASISWI POLTEKKES KEMENKES BANTEN - Hikmah, Ema; Suhanda, Parta (Jurnal Medikes (Media Informasi Kesehatan), 2023)
The COVID-19 pandemic has affected many aspects both physical, social, psychosocial, and economic. Changes during the COVID-19 pandemic in some people will feel shocked, worried, and anxious. For women, changing lifestyles can affect reproductive health, one of which is the incidence of Premenstrual Syndrome. Factors affecting premenstrual syndrome can be both internal and external influences. This study aims to determine the factors associated with the incidence of premenstrual syndrome during the COVID-19 pandemic in female students at the Polytechnic of Health Banten. This study is a quantitative research using a cross-sectional research design, sampling by random sampling, totaling 120 people consisting of 42 female students majoring in nursing Tangerang, 39 female students majoring in ATLM, and 39 people majoring in midwifery. Data were analyzed using bivariate chi-square analysis, and multivariate using logistic regression. The results showed that the stress level factor was significantly related to the incidence of premenstrual syndrome during the COVID-19 pandemic with a p-value of 0.000 (<0.005). After modeling using multivariate analysis, it was found that dietary factors can increase the risk of twice causing the incidence of premenstrual syndrome during COVID-19 after being controlled by stress level factors. It is recommended to women in general and Banten Poltekkes students in particular that a good diet and controlled stress levels can prevent the risk of premenstrual syndrome.